1998
DOI: 10.1016/s0167-1987(98)00142-1
|View full text |Cite
|
Sign up to set email alerts
|

Tillage system effects on 15-year carbon-based and simulated N budgets in a tile-drained Iowa field

Abstract: Tillage influences N fate and transport by changing soil structure, aeration, macropore continuity, plantresidue placement, and organic-matter mineralization rates. Our objective was to use 15-year N budgets to compare four primary tillage treatments for continuous corn (Zea mays L.) production on tile-drained Aquic Hapludolls (FAO: Haplic Phaeozems) in northeastern Iowa, USA. A carbon-based N budget used annual grain yield, grain-N concentrations measured in 1992, changes in surface-soil C content between 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Simulated N fixation for soybean was highest under MP, followed by CP and NT (Table 4) due to higher N uptake demand and higher soybean biomass. Increase in soil organic N was slightly higher with CS compared to CC, which is in agreement with experimental observations (Karlen et al, 1991(Karlen et al, , 1998. The slightly higher soil organic N increase under MP for CS was due to higher soybean yield simulated under MP.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectssupporting
confidence: 90%
See 2 more Smart Citations
“…Simulated N fixation for soybean was highest under MP, followed by CP and NT (Table 4) due to higher N uptake demand and higher soybean biomass. Increase in soil organic N was slightly higher with CS compared to CC, which is in agreement with experimental observations (Karlen et al, 1991(Karlen et al, , 1998. The slightly higher soil organic N increase under MP for CS was due to higher soybean yield simulated under MP.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectssupporting
confidence: 90%
“…The seasonal water table fluctuates from 20 to 160 cm and subsurface drainage tubes/pipes (10 cm in diameter) were installed in the fall of 1979 at 120 cm depth and 29 m apart. A trenchless drain plow was used to install the center drain in each plot and a chain trencher was used to install the drains between the plots (Karlen et al, 1991(Karlen et al, , 1998.…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lksat for these two layers were optimized and listed in Table 2 (Ma et al, 2007b-this issue). Soil carbon pools were calibrated based on measured data assuming all the carbon was in the slow humus pool since the site had very low fertility when the experiments were started in 1978 (Karlen et al, 1991(Karlen et al, , 1998. Microbial population was initialized by running the model using current management practices for Plot #25 and weather data for a course of 26 years.…”
Section: Model Calibrationmentioning
confidence: 99%
“…The results of these studies have been reported in many publications (Bjorneberg et al, 1998;Karlen et al, 1991;Weed et al, 1995;Singh and Kanwar, 1995;Weed and Kanwar, 1996;Singh et al, 1996;Kanwar et al, 1997;Azevedo et al, 1997;Karlen et al, 1998;Kumar et al, 1998a,b;Kanwar et al, 1999;Kumar et al, 1999;Bakhsh et al, 1999Bakhsh et al, , 2000aBakhsh et al, , 2002Karlen et al, 2004;Bakhsh and Kanwar, 2004;Kanwar et al, 2005;. The publications seniorauthored by Singh, Azevedeo, Kumar, and Bakhsh involved the use of models.…”
Section: Goal Of This Special Issuementioning
confidence: 94%